Estudo dos marcadores de consumo alimentar em estudantes do Instituto Federal de Educação, Ciência e Tecnologia Goiano – Campus Posse - Sousa, Auridete Josefa de (2025)
Introduction: Food consumption markers are tools that make it possible to analyze a person's health and their body's ability to absorb nutrients properly. Objective: To characterize the nutritional status and food consumption markers of students enrolled at the Goiano Federal Institute in Posse – GO, seeking to understand the factors that impact their health and eating habits. Methodology: This is an observational, crosssectional, qualitative and quantitative study involving 98 students from the Instituto Federal de Educação, Ciência e Tecnologia Goiano – Campus Posse (IF Goiano), approved by the Research Ethics Committee of the Universidade Federal de Goiás. Data were collected in June 2024 through the application of a form on the Google Forms platform. The questionnaire consisted of anthropometric data of weight and height self-reported by the students at the time of the interview to calculate the Body Mass Index (BMI), sociodemographic data and a questionnaire of food markers from the Food and Nutrition Information and Surveillance System (SISVAN). Descriptive variables were expressed as mean and standard deviation (SD). For comparison between groups, the T-test for independent samples or Mann–Whitney, when appropriate, was used. Statistical significance of p ≤ 0.05 was adopted. Results: The study population consisted of 98 individuals, most of whom were female (59.18%), single (95.92%) and had completed high school (73.47%). The predominant income was between 1 and 2 minimum wages (50.00%). The results indicate that most students were eutrophic, but with a significant presence of overweight and obesity. The dietary pattern revealed high consumption of ultra-processed foods, such as stuffed cookies (61.40% of adolescents versus 36.59% of adults; p=0.026) and instant noodles (49.12% of adolescents versus 29.27% of adults; p=0.077), while the consumption of fruits (68.37%) and vegetables (51.02%) was relatively moderate. The habit of eating meals using screens or electronic devices was frequent (71.43%). The analysis showed a coexistence of healthy and unhealthy behaviors, with a predominance of inadequate eating patterns among of adolescents. It was observed that the greater consumption of ultra-processed foods among participants showed a tendency to higher BMI, although without a statistically significant difference (p=0.796). The lack of cafeterias on campus compromises adherence to a balanced eating plan. Conclusion: Even though a large part of the study population has healthy habits, excessive consumption of ultra-processed foods and the lack of adequate infrastructure can negatively impact students' food security. The findings reinforce the need for public policies aimed at expanding the supply of adequate food within federal institutions and educational interventions that promote healthier food choices.